TONGUE COATING IN PATIENTS WITH GASTROINTESTINAL AND LIVER DISEASES. - Vladimir E. Panov; Assya Krasteva (Peytchinski Publishing, 2012)
It is known that coating on the tongue can be expressed differently - from thin milk diaper, to thick dirty brown blanket, often associated with malodor in the mouth. Some diseases are suspected for causing increased coating of the tongue.The purpose of this study was to investigate and compare the degree of coating of the tongue in patients with gastrointestinal diseases and healthy ones.